Prevalence of Dental Anomalies in Children with Down Syndrome: A Cross-Sectional Study in Makassar City - Syam, Nahdah Zhafirah; Galib B, Nurhaedah H. (Jurnal Penelitian Inovatif, 2024)
Down syndrome is a chromosomal disorder that is often accompanied by intellectual delays and certain physical characteristics, including oral health problems. Children with Down syndrome often show distinctive orofacial characteristics, such as dental anomalies, with an incidence five times higher than the normal population. This study aims to evaluate the percentage prevalence of types of dental anomalies in children with Down syndrome in Makassar City. This study used a descriptive quantitative method with a cross-sectional approach to assess the prevalence of dental anomalies in 41 children with Down syndrome in eight special schools (SLB) in Makassar City aged 6-21 years using a purposive sampling technique. Data were analyzed in the form of frequency distribution and percentage. The results showed that in Makassar City, hypodontia as the most common anomaly (59.6%) occurred, followed by macrodontia (19.1%), microdotia (8.5%), supernumerary teeth (6.4%), fusion (2.1%), enamel hypocalcification (2.1%), and enamel hypoplasia (2.1%). Dental anomalies were more common in boys (63.8%) than girls (36.2%). This study highlights the importance of prevention and early treatment to reduce the risk of complications due to dental anomalies in children with Down syndrome.